Increase in the Inflammatory Marker GlycA over 13 Years in Young Adults Is Associated with Poorer Cognitive Function in Midlife. - Irit Cohen-Manheim (PLoS ONE, 2015)
Inflammatory markers are elevated in patients with dementia. Evidence for an association between inflammation and cognitive function in dementia-free individuals is sparse, inconsistent, and predominantly restricted to the elderly. Assessment of inflammatory markers in young adults as predictors of cognitive function in midlife, well before the onset of overt dementia, is lacking. Furthermore, rarely has the relation with longitudinal change in inflammatory markers been examined.To examine the association of the inflammatory markers C-reactive protein (CRP), fibrinogen, white blood cell count (WBC) and GlycA, a novel NMR-determined biomarker of systemic inflammation, measured in young adulthood and of GlycA change over 13 years follow-up with cognitive function in midlife.507 participants of the Jerusalem Lipid Research Clinic (LRC) study were assessed at 3 time points over 18-22 years. First, the inflammatory variables GlycA, CRP, fibrinogen, and WBC were measured in blood samples drawn at ages 28-32. Then, in blood samples drawn a mean 13 years later (range, 12-16 years) at ages 41-46, GlycA was again measured (in 484 individuals). Subsequently at ages 48-52, on average 7 years later, global cognitive function and its five specific component domains were assessed with a NeuroTrax computerized test battery. Multiple regression and multivariable logistic models were applied.Inverse unadjusted associations were shown for baseline levels and longitudinal change in inflammatory markers and measures of cognition. Multiple regression models were adjusted for age at cognitive assessment, sex, socio-demographic characteristics, baseline measures of leisure-time vigorous activity, smoking status and body mass index (BMI) at ages 28-32, change in smoking status and BMI between ages 28-32 and 41-46, and depression assessed at the time of cognitive testing. The highest quintile of GlycA change, but not the baseline inflammation measures, was inversely related to global cognition (standardized β = -.109, p = .011) as well as to the information processing speed and memory domains (standardized β = -.124, p = .008 and-.117, p = .014, respectively). The multivariable-adjusted odds ratio for low ranked global cognitive function (lowest fifth) comparing the extreme quintiles of GlycA change was 4.8 (95%CI, 1.7-13.5, p = .003; p for trend = .031).In this longitudinal study of a novel systemic inflammatory marker in a population-based cohort of young adults, GlycA increase over 13 years, but not baseline measures of inflammation, was associated with poorer cognitive function in midlife.